Urinary IL-8 and BLCA-4 in detection of bladder cancer and their clinical significant - AL-biaty, Huda Sadoon Jassim (Iraqi Journal of Cancer and Medical Genetics, 2015)
Bladder cancer is a highly prevalent human disease world wide This study of bladder cancer was conducted to assess the significance of level difference in some cancer biomarkers in bladder cancer patients, like IL-8 which is an angiogenic factor associated with inflammation and carcinogenesis and Bladder cancer-associated protein (BLCA4) that is a specific nuclear matrix protein (transcription factor) found in bladder cancer functioning in the regulation of the gene expression related to cell growth. IL8and BLCA4 evaluated in urine of 48 bladder cancer patients and 40 healthy controls by ELISA test, result indicated that urine IL8 and BLCA4 shows high specificity in diagnosis bladder cancer patients, The correlation between IL-8 with BLCA4 showed a significant association in patients with recurrent bladder cancer, urine IL8 and BLCA4 have a role in discrimination between ( newly diagnosed vs recurrence, low grade vs high grade, muscle invasion vs non muscle invasion),but un related to some risk factors like smoking ,Schistosomiasis,Urinary tract infection,stones and family history of cance.